Lightweight and flexible PAN@PPy/MXene films with outstanding electromagnetic interference shielding and Joule heating performance. Issue 48 (30th November 2022) - Wu, Fushuo; Tian, Zhihua; Hu, Peiying; Tang, Jingwen; Xu, Xueqin; Pan, Long; Liu, Jian; Zhang, Peigen; Sun, ZhengMing
Abstract : A simple and effective strategy for preparing lightweight and flexible EMI shielding and Joule heating films was developed. The high SSE/t and efficient Joule heating ability of the films bode potential applications in smart and wearable devices. Abstract : Lightweight and flexible multifunctional materials with excellent electromagnetic interference (EMI) shielding and Joule heating performances are highly demanded for smart and wearable electronics. In this work, polyacrylonitrile (PAN) nanofiber films are prepared by electrospinning and then coated with polypyrrole (PPy) via vapor deposition, yielding a continuous three-dimensional (3D) conductive network of PAN@PPy. Ti3 C2 T x MXene nanosheets with high electrical conductivity are sprayed on the PAN@PPy film to enhance its EMI shielding performance. The as-prepared PAN@PPy/MXene films (55 μm thick) exhibit a high EMI shielding effectiveness (SE) of 32 dB, achieving an extraordinarily high normalized surface-specific SE (SSE/t) of up to 17 534.5 dB cm 2 g −1 from 8.2 to 12.4 GHz; simultaneously, the temperatures of PAN@PPy/MXene films can be driven up to 170.5 °C at an input voltage of 4 V, and exhibit fast-response, stable, and long-term Joule heating performance. The high SSE/t and efficient Joule heating ability of the films bode potential applications in smart and wearable devices.